Methotrexate- and Cyclophosphamide-embedded Pure and Strontiumsubstituted Carbonate Apatite Nanoparticles for Augmentation of Chemotherapeutic Activities in Breast Cancer Cells - Tiash, Snigdha; Othman, Iekhsan; Rosli, Rosita; Hoque Chowdhury, Ezharul (Current Drug Delivery, 2014)
Most of the classical drugs used today to destroy cancer cells lead to the development of acquired resistance in those cells by limiting cellular entry of the drugs or exporting them out by efflux pumps. As a result, higher doses of drugs are usually required to kill the cancer cells affecting normal cells and causing numerous side effects. Accumulation of the therapeutic level of drugs inside the cancer cells is thus required for an adequate period of time to get drugs’ complete therapeutic efficacy minimizing the side effects on normal cells. In order to improve the efficacy of chemotherapeutic drugs, nanoparticles of carbonate apatite and its strontium (Sr2+)-substituted derivative were used in this study to make complexes with three classical anticancer drugs, methotrexate, cyclophosphamide and 5-flurouracil. The binding affinities of these drugs to apatite were evaluated by absorbance and HPLC analysis and the therapeutic efficacy of drug-apatite complexes was determined by cell viability assay. Carbonate apatite demonstrated significant binding affinity towards methotrexate and cyclophosphamide leading to more cellular toxicity than free drugs in MCF-7 and 4T1 breast cancer cells. Moreover, Sr2+ substitution in carbonate apatite with resulting tiny particles less than 100 nm in diameter further promoted binding of methotrexate to the nanocarriers indicating that Sr2+-substituted apatite nanoparticles have the high potential for loading substantial amount of anti-cancer drugs with eventual more therapeutic effectiveness.
Keywords: Cyclophosphamide